State and trait serotonin variations interact to shape the intrinsic connectivity and gradient architecture of the brain – a combined TPH2 genetics and tryptophan depletion study in men - Lan Wang; Congcong Liu; Xianyang Gan; Keith Kendrick; Weihua Zhao; Christian Montag; Ting Xu; Benjamin Becker (Psychopharmacology, 2026)
Rationale Serotonin (5-HT) critically regulates cognitive and emotional functions, and both stable and transient variations in 5-HT signaling have been associated with emotional dysregulations. However, findings regarding the neurofunctional effects of transient 5-HT variations have been highly inconsistent. Objective Therefore, we examined whether individual variations in a central 5-HT-regulating genetic polymorphism (tryptophan hydroxylase 2, TPH2) represent a vulnerability or resilience factor for the effects of acute tryptophan depletion (ATD) on functional brain architecture. Methods The current study utilized a pharmacogenetic within-subject randomized placebo-controlled resting-state fMRI design with N = 53 healthy male participants in combination with spontaneous intrinsic neural activity, functional connectivity, and connectome gradient analyses to compare the neurofunctional effects of ATD-induced transient reduction in central 5-HT signaling between TPH2 genotypes (a priori genotyping for rs4570625, GG n = 25 vs. TT n = 23). Results ATD induced significant increases in spontaneous neural activity in hippocampal CA1 irrespective of genotype and enhanced communication of this region with the bilateral amygdala and the vmPFC specifically in GG carriers. ATD sharpened the intrinsic connectome gradient architecture in several large-scale networks, including the salience, frontoparietal, and default mode network. Conclusions Our results identify a potential genetic marker for an increased vulnerability to the neural effects of transient variations in 5-HT signaling on the functional architecture of an anxiety- and stress-related brain circuit in men. Gradient architecture results underscore the regulatory role of 5-HT on the intricate organization of large-scale networks involved in emotional reactivity and regulation.